THERAPEUTIC APPROACH TO UREMIC PERICARDITIS (International Seven Journal of Multidisciplinary, 2026)
Uremic pericarditis is an inflammatory condition affecting the pericardium in patients with severe renal dysfunction, particularly those with end-stage renal disease. Toxic metabolic byproducts accumulate in the bloodstream, triggering inflammation of this fibroelastic sac. Common clinical features include positional chest pain, a pericardial friction rub, and, in advanced cases, signs of cardiac tamponade. Uremic pericarditis is currently rare due to improved hemodialysis practices, but its decreasing frequency may contribute to delayed diagnosis. Early echocardiographic evaluation is essential in suspected cases to identify pericardial effusion or hemodynamic compromise. Although most patients improve with intensification of dialysis, some require surgical intervention, such as pericardiocentesis or the creation of a pericardial window, to relieve tamponade or obtain tissue for diagnostic purposes.